2022
DOI: 10.1002/pchj.593
|View full text |Cite
|
Sign up to set email alerts
|

Awe in the workplace promotes prosocial behavior

Abstract: In the existing literature on awe, many research findings indicate the positive impact of awe on prosocial behavior. However, very few studies have examined awe in organizational contexts, and researchers have neglected to investigate the effect of awe induced by workplace elicitors. In a between-subject experimental study (N = 264), we introduced awe elicited by work factors, and examined its effect on prosocial intention and behavior (as compared with the neutral emotion condition and pleasantness condition)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Studies suggest humans experience awe several times weekly 78,79 in response to stimuli we broadly encounter throughout our lives. 75 People can feel awe in response to moving acts of kindness, to green space, or even to occupational triggers requiring accommodation 80 such as when a bad outcome occurs despite impeccable effort, planning, or teamwork. For teams and collectives, awe facilitates individuals feeling as though they are a small part of a bigger picture, engage in teamwork, and participate as members of larger groups.…”
Section: The Potential Of Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest humans experience awe several times weekly 78,79 in response to stimuli we broadly encounter throughout our lives. 75 People can feel awe in response to moving acts of kindness, to green space, or even to occupational triggers requiring accommodation 80 such as when a bad outcome occurs despite impeccable effort, planning, or teamwork. For teams and collectives, awe facilitates individuals feeling as though they are a small part of a bigger picture, engage in teamwork, and participate as members of larger groups.…”
Section: The Potential Of Failurementioning
confidence: 99%
“…Efforts to develop the skills to share stories of failure, with humility and clarity, could be fruitful. As we know that hearing or reading inspiring stories cultivates awe rather reliably, 74,75,80,104 efforts to develop our educators' ability to recount failure could facilitate awe cultivation in those they share with, thus possibly priming our teams to handle future failures well, with heightened educational impact, and with prosocial ripple effects. Efforts like these could shift the impact of shame away from isolation and embarrassment and toward prosocial, collective outcomes.…”
Section: Destigmatize Failurementioning
confidence: 99%
“…Awe has also been described as a self-transcendent emotion, as the experience can lead to feeling more connected to others and can increase prosocial behaviors (Piff et al, 2015;Bai et al, 2017;Thompson, 2022a). Meng and Wang (2022) have shown that prosocial behaviors increased when awe was elicited in the context of the workplace. Additionally, Thompson and Jensen's (2023) work on awe and the workplace showed how reflecting and sharing work-related awe experiences can support police hostage negotiators' wellbeing, and also demonstrated the direct relationship between awe and negotiator effectiveness.…”
Section: Awementioning
confidence: 99%